7-Fluoro-2-(prop-2-en-1-ylsulfanyl)-3-(1H-1,2,4-triazol-1-yl)-4H-thiochromen-4-one - Liu, Dong-liang (International Union of Crystallography, 2011)
The asymmetric unit of the title compound, C(14)H(10)FN(3)OS(2), contains two independent molecules which differ in the relative orientations of the triazole and allylsulfanyl groups with respect to the planar thiochromen-4-one frameworks. The N—N—C—C torsion angles are 128.2 (5) and −120.9 (5)°, while the C—S—C—S torsion angles are −17.4 (4) and 16.4 (4)°. In the crystal, intermolecular C—H⋯O and C—H⋯N hydrogen bonds link the molecules in a stacked arrangement along the a axis.